The effects of self-talk cues on the putting performance of golfers susceptible to detrimental putting performances under high pressure settings - Marshall, D. V. J.; Hanrahan, S. J.; Comoutos, N. (International Journal of Golf Science, 2016)
This study examined the effects of a self-talk (ST) intervention on golfers and anxiety and the subsequent influence on putting performances. Seven amateur golfers with a history of anxiety when putting were divided into 3 groups (control, motivational ST, and instructional ST) and completed a 10-session ST intervention involving simulated putting. Ratings of anxiety as measured by the CSAI-2R (Cox, Martens, & Russell, 2003) were obtained pre- and post-intervention. Results indicate statistical significance between the three groups with improvements in the putting performance of the instructional ST group, followed by the motivational ST group, then the control group. There were, however, no significant changes in anxiety scores